2017
DOI: 10.1002/app.45440
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the hard‐segment concentration on highly resilient polyurethane foams based on palm olein polyol

Abstract: The impact of replacing polyether polyol with different levels of a palm‐olein‐based natural oil polyol (NOP) was systematically correlated with the changes in the foaming reactivities, cell structures, physicomechanical properties, and morphologies of highly resilient (HR) polyurethane foams. Replacing the polyether polyol with the NOP did not require us to significantly modify the formulation to obtain stabile foams with uniform and open cell structures. The incorporation of the NOP increased the tear streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…The calculation of tan δ resulted in a broad signal with no clear peak observable. Such more or less unusual trajectories have been observed in other studies dealing with PU foam as well [ 75 ]. The simultaneous presence of a chain extender and a cross-linker as well as of two different polyols differing in chain length led to the formation of a polymeric network with a broad length distribution of the chain segments between the netpoints.…”
Section: Resultssupporting
confidence: 73%
“…The calculation of tan δ resulted in a broad signal with no clear peak observable. Such more or less unusual trajectories have been observed in other studies dealing with PU foam as well [ 75 ]. The simultaneous presence of a chain extender and a cross-linker as well as of two different polyols differing in chain length led to the formation of a polymeric network with a broad length distribution of the chain segments between the netpoints.…”
Section: Resultssupporting
confidence: 73%
“…[15][16][17][18][19][20][21][22] Moreover, partial replacement of petroleum-based polyols with biobased polyols is an alternative approach for the preparation of polyurethane for applications such as coatings, adhesives, sealant, elastomer, as well as flexible and rigid foams. [23][24][25][26][27][28][29][30][31][32][33][34][35] The possibility of utilising castor oil and crude glycerol to produce bio-based polyols and subsequently RPUFs was explored by Carrico et al 5 Different amounts and types of blowing agent (water, pentane and cyclo-pentane) and catalyst (DBTDL) were examined in the study. Increase amount of water content resulted in a decrease in density, thermal conductivity, compressive strength and Young's modulus.…”
Section: Introductionmentioning
confidence: 99%
“…Adnan et al used bio-polyol based on palm-olein for the synthesis of high-resilient (HR) polyurethane foams. The conducted research showed that the implementation of vegetable-based polyol up to 25 wt.% did not have any influence on properties of the obtained materials [22].…”
Section: Introductionmentioning
confidence: 99%